Towards Sustainable Water Solutions: Investigating Groundwater Possibility in Dindori District of Madhya Pradesh, India - Pendro, Budhram; Yadav, Yogesh (Integrated Journal for Research in Arts and Humanities, 2024)
Groundwater is a crucial resource, as approximately 45% of irrigation and around 80% of domestic water needs in India are fulfilled by groundwater reservoirs. Therefore, it is essential to determine where the probability of groundwater availability is high and where it is low. In areas with low probability, there is a need for the rapid development of recharge structures. GIS and remote sensing technology is a crucial tool for obtaining information about availability of ground water potential as well as finding suitable site for recharge structures. The investigation will involve geological surveys to understand the hydrogeological characteristics of the region, including aquifer properties, recharge mechanisms, and groundwater quality. Additionally, environmental impact assessments will be conducted to evaluate the sustainability of groundwater extraction and its potential implications on the surrounding ecosystems. Furthermore, socio-economic analyses will explore the existing water usage patterns, community needs, and stakeholders' perspectives to develop inclusive and equitable groundwater management plans. "This study focuses on the Dindori district in Madhya Pradesh, India. There are different factors affecting groundwater recharge, including topography, slope, land use and land cover, drainage density, geology, soil distribution, rainfall, lineament, etc. Satellite images provide information about land use/land cover, geomorphology, and DEM delineate slope, drainage, and lineament. They are classified into different classes and assigned weights. ArcGIS software was used for data integration and weighted overlay analysis to create a groundwater potential map for the Dindori district. The groundwater potential map is categorized into five classes: 'Excellent' (0.01%), 'Good' (9.78%), 'Moderate' (70.04%), 'Poor' (19.97%), and 'Very Poor/Nil' (0.17%)."